2020
DOI: 10.1097/txd.0000000000001048
|View full text |Cite
|
Sign up to set email alerts
|

Longer Distance From Dialysis Facility to Transplant Center Is Associated With Lower Access to Kidney Transplantation

Abstract: Background. Rates of kidney transplantation vary substantially across dialysis facilities in the United States. Whether distance between the dialysis facility and transplant center associates with variations in transplantation rates has not been examined. Methods. We performed a retrospective study of adults treated with dialysis between 2005 and 2015, according to the US Renal Data System. We examined the association between distance from dialysis faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies using the USRDS data have demonstrated low rates of addition to the waitlist among women, minorities, patients receiving dialysis at facilities located further away from transplant centers, and the elderly [ 58 60 ]. Among UNOS regions, racial disparities appear to be more pronounced where Black patients comprise a large proportion of the end stage renal disease (ESRD) population [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies using the USRDS data have demonstrated low rates of addition to the waitlist among women, minorities, patients receiving dialysis at facilities located further away from transplant centers, and the elderly [ 58 60 ]. Among UNOS regions, racial disparities appear to be more pronounced where Black patients comprise a large proportion of the end stage renal disease (ESRD) population [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Limited availability of dialysis facilities may limit the access to maintenance dialysis for kidney failure patients and could ultimately impact their health outcomes, such as ability to receive a kidney transplant. 7 Additionally, other work has found longer travel times among kidney failure patients are associated with greater adjusted relative risk of death as well as lower perceived quality of life. 17…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have evaluated the impact of limited dialysis facility access, few studies have investigated the distribution and patient-level characteristics on the basis of availability of dialysis facilities. Limited availability of dialysis facilities may limit the access to maintenance dialysis for kidney failure patients and could ultimately impact their health outcomes, such as ability to receive a kidney transplant (7). Additionally, other work has found that longer travel times among kidney failure patients are associated with greater adjusted relative risk of death and lower perceived quality of life (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation